Effect of various protective solutions on function after kidney transplantation - Hrabalova, Monika; Bachleda, Petr; Lubuska, Lucie; Kojecky, Zdenek; Zadrazil, Josef; Krejci, Karel; Al Jabry, Sadek (Biomedical papers, 2003)
From 1995 to 2002 we monitored a group of 127 patients who had undergone kidney transplantations in the Olomouc transplantation centre. The aim of our study was to assess the function of the kidneys after the transplantation, which were rinsed during the removal from cadaverous donors and afterwards were treated by different preservative dilutions. We divided the patients into three groups of approximate similar size, according to the used dilution - EC (Eurocollins), HTK (Custodiol) and UW (Viaspan). In the first three weeks we assessed in each group, the immediate function of the kidneys as primary, belated and afunction. The EC group showed the primary function in 51.2 % of cases, belated in 46.8 % of cases and afunction in 2.1 % of cases. In the HTK group, primary function was found in 73.7 %, belated 23.6 % and afunction 2.7 %. The results of the UW group came to primary function 71.5 %, belated 26.2 % and afunction 2.3 %. The criteria of the immediate but also the long-term function (five year investigation) was a serum creatinine figure. The lowest decline of creatinine in three weeks after the transplantation was noticed in the EC group (the average figure = 429 umol/l). In contrast the HTK group (the average figure 279 umol/l) and the UW group (the average figure 288 umol/l) had comparable figures and there was no significant difference between them from the statistical point of view. It means later in the first, the third and the fifth year after the transplantation the figures levelled out: EC 154 um/l, HTK 182 um/l, and UW 133 um/l. There was statistically a minimum significant difference between the HTK group and the UW group. Another criteria was to determine the amount of functional grafts in alive donees. The Assessment was carried out always in each year after the transplantation, altogether five years. The amount of the functional renal grafts in EC and HTK group was 100 %, in the UW group 76.9 %.Conclusion: HTK and UW gave better immediate functionality results, but there were no differences found among EC, HTK and the UW group from the long-term point of view.
Keywords: Organ preservation / Protective solutions / Hypothermy / Cellulous ischaemia / Organ removal / Reperfussion / Transplantation